The development and prospects of an academic department in a college of education a case study - Abellera, Paterno M. 1949- ([place of publication not identified] [publisher not identified], 1974)
This case study addresses the problem of obtaining an empirical description of the development of the Department of Educational Administration in the College of Education at the University of the Philippines and to determine its prospects and future role as an academic unit. The study was designed to examine the nature, the structure, the components, the goals and the operating characteristics of the Department and interpret them in the light of the theories and principles of formal organizations by Max Weber and Talcott Parsons.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Keywords: Philippines. University. College of Education. Dept. of Educational Administration